Neurotrophic Actions of Mood-Stabilizers: A Recent Research Discovery and its Potential Clinical Applications - Chen, Guang; Creson, Thomas; Engel, Sharon; Hao, Yanlei; Wang, Gang (Current Psychiatry Reviews, 2005)
Recent in vitro and in vivo studies reveal that mood stabilizers lithium and valproate activate the extracellular signal-regulated kinase (ERK) pathway and the phosphoinositide 3-kinase (PI3K) pathways. The activations of the ERK and PI3K pathways are major signaling mechanisms by which neurotrophic factors modulate neurogenesis, neuronal growth and regeneration, neuronal survival, and synaptic plasticity. Like neurotrophic factors, lithium and valproate promote neurite outgrowth and axonal regeneration in cultured neuronal cells and in injury models utilizing retinal cells, sciatic nerve, and spinal cord. These mood stabilizers also enhance neurogenesis in cultured cortical and hippocampal cells and in the hippocampal dentate gyrus of adult animals. Treatments with these mood stabilizers protect cultured cells against a variety of insults and reduce neuronal loss and associated functional deficits in animal models of Alzheimer's disease, HIV-associated encephalitis and dementia, Huntington's disease, ischemia, and Parkinson's disease. Crosssectional and longitudinal brain imaging studies show that lithium treatment increases brain N-acetyl aspartate levels and cerebral gray matter volumes in patients with mood disorders. These data suggest that mood stabilizers and neurotrophins share common mechanisms of action that may contribute to their therapeutic effects.
Keywords: lithium